Attention-deficit hyperactivity disorder. - Thapar, Ajay K (2003)
Attention-deficit hyperactivity disorder (ADHD) affects between 1.4% and 6% of children. The importance of the role of primary care in the recognition and joint management of this disorder is being increasingly highlighted. Despite a wealth of research, the diagnosis and management of ADHD have attracted a good deal of controversy. In this discussion paper, we focus on the empirical basis for some of the more controversial aspects of ADHD, such as diagnosis (discussing both under- and overdiagnosis), aetiology, outcomes, and the role of psychosocial factors in this disorder. We conclude that, provided the diagnosis of ADHD is made accurately and systematically, there are no good scientific grounds for dismissing the concept of ADHD or for failing to intervene.